A General Strategy to Fabricate Carbon‐Coated 3D Porous Interconnected Metal Sulfides: Case Study of SnS/C Nanocomposite for High‐Performance Lithium and Sodium Ion Batteries. Issue 12 (2nd September 2015) - Zhu, Changbao; Kopold, Peter; Li, Weihan; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : Transition metal sulfides have a great potential for energy storage due to the pronouncedly higher capacity (owing to conversion to metal or even alloy) than traditional insertion electrode materials. However, the poor cycling stability still limits the development and application in lithium and sodium ion batteries. Here, taking SnS as a model material, a novel general strategy is proposed to fabricate a 3D porous interconnected metal sulfide/carbon nanocomposite by the electrostatic spray deposition technique without adding any expensive carbonaceous materials such as graphene or carbon nanotube. In this way, small nanorods of SnS are generated with sizes of ≈10–20 nm embedded in amorphous carbon and self‐assembled into a 3D porous interconnected nanocomposite. The SnS:C is directly deposited on the Ti foil as a current collector and neither conductive additives nor binder are needed for battery assembly. Such electrodes exhibit a high reversible capacity, high rate capability, and long cycling stability for both lithium and sodium storage. Abstract : A novel general strategy for fabrication of a 3D porous interconnected metal sulfide/carbon nanocomposite is proposed, using the electrostatic spray deposition technique without adding any expensive carbonaceous materials such as graphene or carbon nanotubes. Such SnS/C composite exhibits a high reversible capacity, high rate capability and long cycling stability for both lithium and sodium storage.